Identification of a Novel Signature and Construction of a Nomogram Predicting Overall Survival in Clear Cell Renal Cell Carcinoma - Wu, Xiangkun; Zhao, Zhijian; Khan, Aisha; Cai, Chao; Lv, Daojun; Gu, Di; Liu, Yongda (Frontiers in Genetics, 2020)
Background: Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal cell carcinoma (RCC), which accounts for the majority of RCC-related deaths. It is clearly essential to further identify more novel prognostic signatures and therapeutic targets. Material and Methods: We identified differentially expressed genes (DEG) be-tween ccRCC and adjacent normal tissue in GEO database using Robust Rank Ag-gregation (RRA) method. A mRNA signature (mRNASig) based on DEGs was devel-oped using Cox and LASSO analysis in TCGA database and validated in ICGC data-base. Afterward, the influence of mRNASig mRNAs on the immune microenviron-ment in ccRCC was explore using comprehensive bioinformatics analysis. Results: A total of 957 robust DEGs were identified using RRA method. mRNASig comprised CEP55, IFI44, NCF4, and TCIRG1 was developed and validated to identi-fy high-risk patients who had poorer prognosis than low-risk patients. A nomogram was also constructed based on mRNASig, AJCC stage and tumor grade. The 4 mRNAs were closely related to a variety of tumor-infiltrating lymphocytes, espe-cially including CD8+ T cells, activated CD4+ memory T cells, regulatory T cells, activated NK cells and resting NK cells. The 4 mRNAs were also correlated posi-tively with the expression of CTLA4, LAG3, PDCD1, TIGIT, and HAVCR2. Conclusions: We developed and validated mRNASig to assist clinicians in making personalized treatment decisions. Furthermore, CEP55, IFI44, NCF4 and TCIRG1 may be novel potential targets for future treatment of ccRCC.